Penggunaan Media Video Animasi Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Geografi Kelas X Di SMA Negeri - Nuhu, Wa Nuhu; Hariyadi, Eko; Kamur, Sudarwin; Awal, Samsi; Iskandar, Ahmad; Nanda Kharisma, Gaby (Mataram University, 2024)
Abstrak: Between April and May of 2024, this study was carried out at SMA Negeri 2 Gu. Finding out how the usage of animated video learning materials affects class X geography students' learning results is the aim of this study. A one-grub-post-experiment pre-experiment design was used to conduct the study. where 32 pupils in a single class make up the sample. The pretest and posttest, which both consisted of essay-style questions, provided the research data. There are two sections to the data analysis that was done. Using the t-test formula, the first phase of the data analysis is descriptive statistical analysis, followed by inferential statistical analysis.Descriptive statistics of the research from two samples, on the pretest and postest data, were presented in the first study's results. In the second trial, the average pretest score was 58.90, and the average posttest score was 85.93. It can be inferred that Ha was accepted and Ho was not rejected because the substantial difference between the pretest and posstest results was demonstrated by the significant result value of 0.00 ≤ 0.05. Consequently, it can be said that the utilization of animated video content affects the geography learning outcomes of class X students at SMA Negeri 2 Gu.